Hubungan Jarak Kehamilan dan Pekerjaan Ibu dengan Kejadian Abortus di Rsia Ananda Makassar Tahun 2021 - Muhammad Dahlan; Khadiamsi, Aura Audhilla; Najamuddin; Rahim, Rosdianah; Sakti, Dachlia Sri (Alami Journal (Alauddin Islamic Medical) Journal, 2024)
Maternal mortality is a health problem in Indonesia as the number of cases is relatively high at 7.389 cases which the main cause being bleeding, especially abortion bleeding in young pregnancies. The purpose of this study was to determine the influences of inter-pregnancy interval and the working load of mothers on the occurrences of abortion at RSIA Ananda Makassar in 2021. This research also attempted to investigate the most dominant risk factors causing abortion. The methodological approach used in this research was quantitative analytical research with a case-control design. The sampling method was a purposive sampling technique consisting of 234 samples divided into 117 case samples and 117 control samples obtained from medical record data. The findings of this Chi-square analysis test indicated that the p-value of pregnancy interval and occupation was 0.000 (p<0.05), and the results of the multiple regression test showed an OR value of 3.018 for the occupational variable. Therefore, this study concluded that there were significant influences of the inter-pregnancy interval and maternal occupation on the abortus incidence at RSIA Ananda Makassar in 2021, with the inter-pregnancy interval being considered the most dominant risk factor for abortion.